Pengaruh Sitokinin (Kinetin) dan Auksin (2,4-D) dalam Media Induksi Murashige dan Skoog terhadap Perkembangan Eksplan Meristem Apikal Tunas Anakan Tanaman Sagu (Metroxylon sagu Rottb.) - Nurhidayah, Tengku; Mardhiansyah, Muhammad; Mulyani, Desti (Jurnal Agro Teknologi Tropika, 2017)
This research aims to observe the effect of the concentration combination of cytokines (Kinetin) and auxin (2,4-D) in the induction medium MS to the development of the apical meristem explant shoots chicks of sago plant suckers. The research was carried out in the Laboratory of Plant Biotechnology Department of Agrotechnology Faculty of Agriculture, University of Riau, from October 2014 to January 2015. The experimental units were arranged in a completely randomized design consisting of six treatments: P1 = 0.1 mg/l kinetin + 5 mg/l 2,4-D; P2 = 0.1 mg/l kinetin + 10 mg/l 2,4-D; P3 = 0.1 mg/l kinetin + 15 mg/l 2,4-D; P4 = 0.2 mg/l kinetin + 5 mg/l 2,4-D; P5 = 0.2 mg/l kinetin + 10 mg/l 2,4-D; P6 = 0.2 mg/l kinetin + 15 mg/l 2,4-D and were replicated three times. Data were analyzed using analysis of variance and further analyzed with Duncanâs New Multiple Range Test at 5 % level. Parameters measured were shoot emergence time (days), number of shoots, shoots height (cm) and the number and percentage of shoots contaminated (%). The results showed that the addition of some concentration of kinetin and 2,4-D in MS induction medium affected on the development of the apical meristem explant shoots chicks of sago plant suckers. The best development of the apical meristem explant shoots of sago plant suckers was found on the combination of kinetin 0.2 mg/l + 10 mg/l 2,4-D.